Application of Google Earth Engine for Agriculture Drought Monitoring in East Lombok - Robbaniyyah, Nuzla Af'idatur; Hidayatunnisa, Nurul; Maharani, Rani; Ulfa, Kurnia; Alfian, Muhammad Rijal (Program Studi Matematika, 2025)
In tropical regions such as East Lombok Regency, where food production is highly dependent on rainfall, drought poses a major threat to the agricultural sector. This study aims to monitor drought patterns over time using Google Earth Engine (GEE). Vegetation indices, including the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and Normalized Difference Drought Index (NDDI), were derived from Landsat 8 satellite imagery. The analysis revealed that during the dry season, particularly in August and September, the southern region—especially Jerowaru Sub-district—experienced severe drought conditions. The western parts, including Sambelia, Pringgabaya, and Suela Sub-districts, were also significantly affected, with the most impacted areas being rain-fed rice fields, corn plantations, and mixed horticultural crops. Temporal trend analysis indicated an increasing drought intensity in the later years of observation. The resulting information can support decision-making in drought risk mitigation and sustainable water resource management. By integrating satellite-based drought assessment with agricultural planning, this approach can strengthen food security and promote adaptive agricultural practices in drought-prone regions such as East Lombok Regency.